A conceptual change in crystallisation mechanisms of oxide materials from solutions in closed systems - Kelly, John; Chullanayil Padmanabhan, Sibu (My University, 2020)
Atomic and molecular level interactions in solutions dictate the structural and functional attributes of crystals. These features clearly dictate the properties of materials and their applicability in technologies. However, the microscopic phenomena of particle formation—nucleation and growth—in real systems are still not fully understood. Specifically, crystallisation occurring in closed systems are largely unproven. Combining coherent experimental data, we here demonstrate a fundamental nucleation-growth mechanism that occurs in a model zinc oxide system when particles are formed under continuous, rapid heating under closed reaction conditions. Defying all previous reports, we show that the nucleation commences only when the heating is terminated. A prenucleation clusters pathway is observed for nucleation, followed by crystallite assembly-growth. We show that the nucleation-growth processes result from temporal and dynamic activity of constituent ions and gaseous molecules in solution and by the irreversible expulsion of the dissolved gaseous molecules. We suggest that this nucleation process is generic to most closed systems that go through precipitation, and, therefore, important for the crystallisation of a variety of metal oxides, composites and minerals. We anticipate that the work may be a platform for future experimental and theoretical investigation promoting deeper understanding of the nucleation-growth phenomena of a variety of practical systems.
PUBLISHED
Keywords: crystallisation; particle formation; nucleation and growth; crystallisation; particle formation; nucleation and growth; Nanoscience & Materials